A density functional theory study of the hydride shift in the Eschweiler–Clarke reaction. (31st May 2021) - Yamabe, Shinichi; Tsuchida, Noriko; Yamazaki, Shoko
Abstract: The Eschweiler–Clarke (the amine methylation) reaction was investigated by density functional theory (DFT) calculations. First, a reaction model of H3 CNH2 + HC(O)OH + CH2 O + (H2 O)3 → (H3 C)2 NH + CO2 + (H2 O)4 was employed for geometry optimizations. Geometries and activation free energies of transition states (TSs) by eight DFTs, B2PLYP‐D3, B3LYP, B3LYP‐D, BP86‐D, PBE0‐D, M06‐2X, wB97X‐D, and APF‐D, along with MP2 were compared. Four elementary processes were obtained. The rate‐determining step is of the hydride‐transfer TS, H3 CN + HCH2 + HCO2 − → H3 CNHCH3 + CO2 . Whereas BP86‐D and APF‐D gave underestimated energies, M06‐2X was found to be a reasonable DFT to trace the present reaction. Second, by the use of M06‐2X/6‐311++G**, hydride‐shift TSs were examined for various sizes of the water cluster (H2 O) n, and the controversial two mechanisms were evaluated. It was suggested that the first formic acid contributes to formation of the iminium ion H3 CN + HCH2 and the second formic acid works for the hydride transfer. The Eschweiler–Clarke reaction was described by the scheme, R 1 R 2 NH + H2 CO + (HCOOH)2 + (H2 O) n → R 1 R 2 NCH3 + CO2 + HCO2 − + H3 O + (H2 O) n . Abstract : The Eschweiler–Clarke reaction was investigated by density functional theory (DFT) calculations. Transition states (TSs) by eight DFTs were assessed. The reaction may be described newly by the equation, R 1 R 2 NH + H2 CO + (HCOOH)2 + (H2 O) n → R 1 R 2 NCH3 + CO2 + HCO2 − + H3 O + (H2 O) n .